CLINICAL AND METABOLIC CHARACTERISTICS AND SPECTRUM OF COMPLICATIONS IN PATIENTS FOLLOWING BARIATRIC SURGERY - B.M. Iminov; Sh.N. Kadirov; B.U. Iriskulov (Journal of modern medicine, 2026)
Surgical treatment of morbid obesity is recognized as highly effective; however, bariatric procedures may induce profound anatomical and functional changes in the gastrointestinal tract. These alterations can contribute to the development of both early and long-term metabolic disorders, the severity of which depends on the type of surgical procedure, the patient’s baseline nutritional status, the dynamics of weight loss, and the quality of postoperative medical follow-up. The main objective of the study was to analyze the clinical and metabolic characteristics of patients after bariatric surgery, determine the structure and major causes of postoperative complications, and identify prognostic markers for their early detection. A comprehensive assessment of clinical, anthropometric, and biochemical parameters was performed, with particular attention to protein, carbohydrate, and lipid metabolism, as well as vitamin and mineral status. Special emphasis was placed on changes in body weight and body mass index, glycemic control, protein status, and the metabolism of iron, calcium, vitamin D, and other micronutrients. The results demonstrated that postoperative metabolic changes are heterogeneous. In addition to the expected reduction in body weight and improvement in several metabolic indicators, some patients developed nutritional deficiencies, anemia, disturbances in protein and mineral metabolism, alterations in bone metabolism, and functional gastrointestinal disorders. The severity of these abnormalities was determined by a combination of contributing factors and required evaluation not only of the immediate surgical outcome but also of the long-term metabolic adaptation of the body. The findings confirm the importance of personalized long-term follow-up with regular assessment of nutritional and metabolic status. Timely detection of laboratory markers associated with an unfavorable outcome and individualized correction of identified abnormalities provide a pathogenetically substantiated strategy for preventing delayed metabolic complications. Such an approach contributes to improving the overall effectiveness and safety of bariatric treatment.